Proyecto de factibilidad para la creación de una empresa productora y comercializadora de siete harinas en la ciudad de Loja - Sánchez Iñiguez, Jhoder Daniel (2018)
In the city of Loja, its inhabitants are exposed to countless consumable products that do not provide vitamins, minerals and other essential nutrients for a healthy life at all, this fact is a consequence of the lack of companies that produce healthy food. In particular, the present thesis work entitled "PROJECT OF FEASIBILITY FOR THE CREATION OF A PRODUCING AND COMMERCIALIZING COMPANY OF SEVEN FLOURS IN THE CITY OF LOJA" was established. Its main objective is to determine the viability of undertaking a food-producing enterprise indispensable in the diet of the community. Through a market study it was determined that of the 269 flour suppliers in Loja, only 70 marketed 7 flours, at an approximate volume of 2 quintals per month and an estimated price of USD 60. Additional questions allowed to establish aspects such as the presentation that should have the product, in this case it will be in a bag of 45.45 pounds. Regarding the competition it was evident that they sell between 50 and 100 quintals per month of 7 flours, at a price of USD 60, therefore the offer does not cover the whole market. The potential demand is 269 buyers of flours for year 1, however some already market 7 flours for which the actual demand to 199, which will acquire an average of 33 quintals per year, giving a real demand of 6.569 quintals per year, but 498 quintals are currently being offered, which implies an unsatisfied demand of 6,071 quintals; for this reason and according to the installed capacity of the company, it is considered pertinent to produce 5,460 quintals per year, which implies the use of 75% of the installed capacity, which will increase by 5% per year until year 5. The technical study allowed to establish the installed capacity that the company will have, the selected location will be in the canton of Loja, Jipiro Alto neighborhood, in virtue that this town shows easy access to the city center and is equipped with all the basic services essential for the company. The fixed assets to be acquired were established in the initial investment, detailing the amount and value of the same by area of work, the raw material requirements were established in accordance with the unsatisfied demand, to avoid monopolizing the local market or producing 7 Flours The administrative study addresses management issues, since it includes the regulations that will govern the human talent of the company, to maintain optimal levels of control and eradicate possible errors and risks that arise, it was established to hire 7 people to fill the vacancies of the company, among which are: Manager, Secretary, Accountant, Saleswoman, Production Manager, Worker and Guard. The financial study showed encouraging results since the various financial planning and evaluation procedures of the project determined the financial relevance, corroborating the feasibility for the creation of the factory, during the 5 years of project life the cash flows are positive and cover appropriately the costs and expenses of the factory, The NPV shows that during the 5 years of the investment total surpluses will be obtained for $40.430,49 exceeding the initial investment made, additionally the IRR shows that the yield is 23.44% a percentage higher than the offered in the financial sector, the benefit-cost ratio obtained a value of 1.20 which implies a profit of $ 0.20 on the total costs, the initial investment will be recovered after 2 years 9 months and 13 days after the start of the productive operations and the sensitivity showed that possible decreases in revenues or increases in costs do not affect The company's profitability is usually the same as this indicator in none of the cases exceeded 0.99. Finally, the environmental impact study was carried out, which addresses the various risks to which the company and its surrounding community are exposed, including competition, generation of work, pollution, local economic development, occupational hazards. , ecology, determining that the company does not promote risks and, on the contrary, benefits the sector where it will operate and its inhabitants.